Going Circular: Uncovering the Spatial Potential of Circular Economic Theories Inspired by Urban Vernacular Environments - Davey, Calayde Aenis (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2021.